PENERIMAAN PEROKOK DAN MANTAN PEROKOK TERHADAP PERUBAHAN LABEL PERINGATAN BAHAYA ROKOK - Dewi, Rizma Nurhadiana (Dakwah, 2017)
This research started based on the health warning label change on the Indonesian cigarette packaging. A qualitative approach used in this research with a reception analysis method. The data on this research collected by a semi-structurized interview about the health warning labels on the cigarette package. The result shown there is no difference between smokers and ex-smokers when they perceived the message on the health warning labels. Their reception toward the message are fully formed by each social experiences, culture, current social facts, society, perception and knowledges around them. The reception of the informants then categorized by Stuart Hall?s Reception Analyze theory which consists of three readings: dominant-hegemonic, negotiation and opposition.